Analisis Efektifitas Biaya dalam Terapi Jamu Saintifik dan Konvensional untuk Terapi Dispepsia - Nurhaliza, Inta; Prasuma, Galar Sigit; Sugiantoro, Ergia Andang; Lianawati, Lianawati; Sutheeraprasert, Praewthip; Setiawan, Didik (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Dyspepsia is a common digestive disorder among global health problems. This study aimed to examine the cost-effectiveness of scientific herbs in the treatment of dyspepsia. This study has used a societal perspective, but the indirect costs are considered equal because the patient is undergoing outpatient care. The analysis was used to determine the cost-effectiveness using the Incremental Cost-Effectiveness Ratio (ICER) method. The results were reported in rupiah currency, which includes categories of direct medical costs and direct non-medical costs. Sensitivity analysis reported changes in results, taking into account various possible influencing variables. A total of 62 patients who were respondents in this study were included in scientific herbal therapy (48.38%) and conventional dyspepsia therapy (51.62%). The cost of scientific herbal therapy was higher than conventional dyspepsia therapy (45.558±4.351 vs. 39.202±4.500). However, this difference was not statistically significant on the effectiveness of therapy (96.67% vs. 90.62%; p-value 0.600), the utility index of scientific herbal medicine was greater than conventional dyspepsia therapy (0.85±0.11 vs. 0.74±0.14). The ICER value for 1 additional unit of effectiveness was IDR 105,933; while for the addition of 1 unit of quality of life was IDR 57,781. The effectiveness of scientific herbal medicine therapy for dyspepsia was greater than the effectiveness of conventional dyspepsia therapy, where the cost was higher but the effectiveness was better.